2020
DOI: 10.1097/tp.0000000000003162
|View full text |Cite
|
Sign up to set email alerts
|

Experience With LDLT in Patients With Hepatocellular Carcinoma and Portal Vein Tumor Thrombosis Postdownstaging

Abstract: Background. Median survival in patients with hepatocellular carcinoma (HCC) and portal vein tumor thrombosis (PVTT) is 2–6 months; conventionally liver transplantation is contraindicated. Methods. We studied outcomes following living donor liver transplantation (LDLT) post-PVTT downstaging (DS) with stereotactic body radiotherapy (SBRT), and tumor ablation (with transarterial chemo- or radio-embolization). Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 53 publications
0
60
0
2
Order By: Relevance
“…During this period, 481 LDLT's were performed in HCC-cirr patients. Forty-six had segmental or lobar portal vein tumour thrombosis, and underwent downstaging before LDLT as per our Institutional protocol [18] . Those 46 patients were excluded from this study.…”
Section: Study Cohortmentioning
confidence: 99%
“…During this period, 481 LDLT's were performed in HCC-cirr patients. Forty-six had segmental or lobar portal vein tumour thrombosis, and underwent downstaging before LDLT as per our Institutional protocol [18] . Those 46 patients were excluded from this study.…”
Section: Study Cohortmentioning
confidence: 99%
“…HAIC: hepatic arterial infusion chemotherapy; IFN-alpha 2b: interferon alfa-2b; LT: liver transplantation; RT: radiation therapy; TACE: transarterial chemoembolization; TARE: transarterial radioembolization; 5-FU: 5-fluorouracil. *Under certain conditions; **not enough support [26,34,35,38,37,40,41] long-term survival outcomes among carefully selected patients under specific criteria such as: (a) PVTT in a segmental branch, (b) AFP level < 100ng/mL, (c) low AP score, and (d) patients with HCC and PVTT who were successfully downstaged [36,42,43] .…”
Section: Vascular Invasionmentioning
confidence: 99%
“…The authors found tumor thrombus extension into the main portal vein, elevated AFP, and tumor size greater than 7 cm to be independent risk factors for recurrence. In the largest study to date, 46 patients with PVTT underwent LDLT after a downstaging protocol using stereotactic body radiation in combination with transarterial chemo-embolization or transarterial radio-embolization [42] . Five-year recurrence free survival and overall survival rates were 51% and 57%, respectively.…”
Section: Vascular Invasionmentioning
confidence: 99%
“…However, recent studies showing successful results with TARE in patients with PVTT were published. We would like to share our experience about the effectiveness of LDLT after downstaging (DS) in patients with HCC and PVTT in the light of the recent paper published Soin and colleagues [ 3 ]. We also would like to emphasize some of the overlooked points we found in their study, based on the experiences we have gained from about 2750 LT including 415 patients with HCC.…”
mentioning
confidence: 99%
“…The authors state that they perform liver biopsy to 2% of the patients with HCC [ 3 ]. Biopsy is not required for the diagnosis of HCC provided that multidetector computerized tomography (MDCT), magnetic resonance imaging (MRI) and alfa-feto protein (AFP) are evaluated all together.…”
mentioning
confidence: 99%